2004
DOI: 10.1590/s1517-86922004000500008
|View full text |Cite
|
Sign up to set email alerts
|

Reabilitação física no transplante de coração

Abstract: After heart transplantation patients improve their quality of life. However, they frequently have clinical problems in the post operative period, as physical deconditioning, muscular atrophy, weakness and lower maximal aerobic capacity, in part due to the inactivity in the preoperative period and to factors as the difference in donor/receptor body surface, heart denervation, among others. Regular physical activity plays an important role in heart transplanted patients follow-up and should be recommended as soo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 22 publications
0
10
0
14
Order By: Relevance
“…Moreover, the breathing efficiency is also improved during exercise [26]. These individuals showed that when implementing a basic program of mobilization and respiratory physiotherapy, they were able to recover the values of lung volumes and capacities and to improve useful functional capacity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the breathing efficiency is also improved during exercise [26]. These individuals showed that when implementing a basic program of mobilization and respiratory physiotherapy, they were able to recover the values of lung volumes and capacities and to improve useful functional capacity.…”
Section: Discussionmentioning
confidence: 90%
“…However, often present physical deconditioning, atrophy and muscle weakness and reduced aerobic capacity, resulting in part from inactivity and preoperative factors such as differences in body surface donor/recipient and denervation of the heart [26]. Regular physical activity has an important role post-transplant and should be started early for the restoration of physical capacity, enabling to patients to back to perform most of their daily activities and also recreation.…”
Section: Discussionmentioning
confidence: 99%
“…Прирост и нормализация ФР после ТС были более значимы у физически активных пациентов. Среди факторов, приведших к улучшению ФР, выделяют: улучшение функции сердечно-сосудистой системы и утилиза-ции кислорода в мышцах [11,21,22]. Полученные данные согласуются с исследованиями Европей-ского сообщества кардиологов (European Society of Cardiology), где показано, что у физически актив-ных пациентов уровень ФР нормализуется быстрее, чем у ведущих сидячий образ жизни [23].…”
Section: Discussionunclassified
“…В настоящее время обсуждаются факторы, ко-торые могут влиять на динамику ФР. К ним можно отнести хронотропную недостаточность, низкую физическую активность или сидячий образ жиз-ни, низкую мышечную массу, а также побочные эффекты применения иммуносупрессивной тера-пии [10,11].…”
Section: Introductionunclassified
“…But also often have physical deconditioning, muscle weakness and atrophy and lower aerobic capacity [27]. Regular physical activity plays an important posttransplant role and should be started early to restore physical capacity, enabling transplanted patients back to perform most of their daily activities and also recreation.…”
Section: Discussionmentioning
confidence: 99%